(untitled) (Dhaka University Journal of Biological Sciences, 2024)
For the past few years, the intensity of dengue in Bangladesh has been rising. The current study was done among 533 dengue patients hospitalized in 2021 in Dhaka to observe the different aspects of clinical manifestations and seasonal occurrence of dengue. Due to COVID-19 restriction, hospital entry and face-to-face interview of the patients was not possible. Hence, contact numbers of the hospitalized dengue patients were collected from Directorate General of Health Services (DGHS) and patients were interviewed over the phone. Out of 533 patients, majority were from Dhaka south city corporation (DSCC) (53.7%), had a monthly household income of 30001≥ BDT (67.4%), and lived in small sized families (76.9%). High fever (p=0.013), headache (p<0.001), body pain (p<0.001), vomiting/nausea (p=0.0085), skin rash (p=0.033), eye lesion/red eyes (p=0.0011), pleural effusion (p=0.0404), weakness (p=0.017) and gum bleeding (p=0.014)- were significantly associated with age groups whereas vomiting/nausea (p=0.048), skin rash (p=0.002) and eye lesion/red eyes (p=0.032) were significantly associated with gender. 86.7% suffered from thrombocytopenia (<150000 per microliter blood), while 27% were in serious condition with lowest platelet count ≤ 20000 per microliter blood. 3.6% patients were admitted to ICU and 1.7% died of dengue. Death due to dengue was significantly associated with age groups (p <0.05) and majority among them were children (≤ 10 years). Family members of 44.6% patients were also affected with dengue and majority of the patients belonged to small sized families. Dengue occurrence had significant association with season where majority of the patients were from monsoon season (65.29%) followed by post-monsoon (33.21%) season. Dengue manifests a wide spectrum of symptoms as shown by the study, so now it is necessary to identify the changes in pattern of the clinical manifestations, and effective disease management to lessen the severity of the outbreak. Dhaka Univ. J. Biol. Sci. 33(1): 33-46, 2024 (January)